Generator loads study of a hydro-electric power house structure - Bakhteri, Jahangir (Penerbit UTM Press, 2003)
The shape of a hydro-electric (hydel) power station particularly the concrete around spiral case and generator foundation is so complex that the determination of actual stresses is very complicated and time-consuming process since it is essentially a three-dimensional problem. The stress variations in the structure have been studied using three-dimensional photoelastic method in few small scale models only. In the present study, finite element and boundary element analyses of spiral (scroll) case and generator foundation of a large hydel power station considering generator loads have been carried out. A simple and efficient method of slices for the geometric representation of the structure has been developed. Linear elastic analyses have been carried out using well established existing finite element and boundary element computer programs and two pre-processing computer programs have also been developed to support the 3-D finite element program. Almost all of the present analyses show the same pattern of stresses and only their values differ, while most of the existing photoelastic study results indicate stresses with different pattern. In conclusion, a suitable, efficient and appropriate numerical method for the approximate analysis of the structure has been proposed.